IMPLEMENTATION OF E-CRM UP-SELLING AND CROSS - SELLING STRATEGY AT MITRA SEJAHTERA STORE - Nur Adlina; Afrisawati Afrisawati; Indra Ramadona Harahap (JURTEKSI (Jurnal Teknologi dan Sistem Informasi), 2023)
Abstract: The development of information technology has experienced a very rapid growth, especially the internet. The Internet makes a very helpful contribution in a business field. Fierce business competition and the rapid growth of information technology make it easy for customers to switch to other stores. Mitra Sejahtera has not implemented a service that makes it easier for customers to buy goods easily and still uses the service manually, sales report data is still used in the general ledger so it is not efficient to do neatly organized records, customers must come directly to the store to find out what products are sold then customers do not know the latest discounts and products sold in stores. Mitra Sejahtera is a beauty business venture that sells brand products such as, wardah, emina, implora, garnier, etc. One of the efforts in improving services is by applying the concept of Customer Relationship Management (CRM) and implementing Up-Selling and Cross-Selling strategies. The goal achieved in this stage is the operability of the results of the system design that has been made. With this CRM design and Up-Selling and Cross-Selling strategy, it can increase sales in meeting customer needs. This system was created to make it easier for Toko Mitra Sejahtera to sell products, process data in a computerized manner and can improve service to customers. Keywords : cosmetics;  electronic customer relationship management (E-CRM); up-selling and cross-selling strategies Abstrak: Perkembangan teknologi informasi telah mengalami pertumbuhan yang sangat pesat terutama internet. Internet memberikan kontribusi yang sangat membantu dalam bidang bisnis. Persaingan bisnis yang ketat dan pesatnya pertumbuhan teknologi informasi memudahkan pelanggan untuk beralih ke toko lain. Mitra Sejahtera belum menerapkan layanan yang memudahkan pelanggan untuk membeli barang dengan mudah dan masih menggunakan layanan secara manual, data laporan penjualan masih digunakan dalam buku besar sehingga tidak efisien untuk melakukan pencatatan yang tertata rapi, pelanggan harus datang langsung ke toko untuk mengetahui produk apa yang dijual maka pelanggan tidak mengetahui diskon terbaru dan produk yang dijual di toko. Mitra Sejahtera adalah usaha bisnis kecantikan yang menjual produk brand seperti, wardah, emina, implora, garnier, dll. Salah satu upaya dalam meningkatkan pelayanan adalah dengan menerapkan konsep Customer Relationship Management (CRM) dan menerapkan strategi Up-Selling dan Cross-Selling. Tujuan yang dicapai pada tahap ini adalah operabilitas hasil desain sistem yang telah dibuat. Dengan desain CRM ini dan strategi Up-Selling dan Cross-Selling, dapat meningkatkan penjualan dalam memenuhi kebutuhan pelanggan. Sistem ini dibuat untuk memudahkan Toko Mitra Sejahtera dalam menjual produk, mengolah data secara komputerisasi dan dapat meningkatkan pelayanan kepada pelanggan. Kata Kunci : kosmetik;  manajemen hubungan pelanggan elektronik (E-CRM); strategi up-selling dan cross-selling